THE MODEL OF JUSTICE AND COMMITMENT IN THE EVALUATION OF STUDENT’S PERFORMANCE (Jurnal Manajemen dan Kewirausahaan, 2014)
This study aimed to examine the importance of justice in students’ performance evaluation which might foster students’ commitment to lecturers, and as a consequence students would perform well. The research was conducted on students from departments of Sebelas Maret University who had undertaken com-petency-based learning; and used stratified sampling. Regression analysis was used to test the hypotheses. The results showed that students’ commitment to lecturers did not significantly influence students’ performance. Distributive and procedural justice in controlled commitment did not significantly influence students’ performance. On the other hand, procedural and distributive justice significantly influenced students’ com-mitment to lecturers.